Academic Dentistry: You Might Be Surprised - Terry Hoover; Parvati Iyer; Laura Reid; Kim Benton; Mythili Kalladka (Journal of the California Dental Association)
Objective This article is meant to spark interest in readers of the rich experiences that Academic Dentistry can offer as a career pathway for dentists. Opportunities have evolved in the last 20 years making it more appealing financially full-time or it can be a compatible hybrid with other pathways such as private or corporate dentistry, public health, community clinic dentistry, or research.Methods Each of the five authors came to Academic Dentistry at different stages and from diverse expectations in their professional lives. These disparate histories are presented to provide a full and rich perspective on Academic Dentistry. Both challenges and rewards in academic are discussed.Conclusions Academic Dentistry, whether entered early or late in one’s professional life, or in combination with another pathway, may provide opportunity for renewal of one’s interest and enjoyment in the dental profession. With many individuals choosing to stay in the workforce longer, academics may increase longevity of career as well. With data indicating the actual shortage of dental faculty and the continuing expansion among dental schools, opportunities to join academics are available.